Cellular Distribution of Bioaccumulated Toxic Heavy Metals in Aspergillus Niger and Rhizopus Arrhizus - TAPAN KUMAR PAL,; SAURYYA BHATTACHARYYA,; ARUNABHA BASUMAJUMDAR, (International Journal of Pharma and Bio Sciences, 2010)
A cadmium tolerant strain of Aspergillus niger and a lead tolerant strain of Rhizopus arrhizus were studied for distribution of accumulated toxic heavy metals in the mycelia in comparison to wild type strains. Accumulated cadmium in the cell wall fractions of cadmium tolerant Aspergillus niger was more than the wild type strain. Cytosolic fraction contained the next highest load of metal. Similar was the observation with lead tolerant Rhizopus arrhizus during bioaccumulation of lead. The results indicated contribution of the surface property of the fungus in metal bioaccumulation. Involvement of the cellular metabolism during metal bioaccumulation and distribution in the sub-cellular compartments was substantiated by the use of some metabolic inhibitors during growth in presence of metals. It was also observed that about 65% of the cell wall bound cadmium in Aspergillus niger and about 79% of the cell wall bound lead in Rhizopus arrhizus were recovered by Ethylene diamine tetra acetic acid (EDTA) treatment, which indicated that the accumulated metals generally reside in the outer surface of the fungi, which could be recovered easily for possible commercial applications.